From Mystical Linguistics To Computational Linguistics - krazdi, zineb; lehouimel, Badis (El Omda in Linguistics and Discourse Analysis, 2023)
Abstract : This article aims to research in Gnostic Linguistics, and examines the ways of acquiring language and its relationship to the human mind, under what is known as the conceptual metaphor theory. So, mystical linguistics came to give importance to the deliberative dimension and is based on the link between linguistic knowledge and thinking and combines a group of disciplines, the most important of which are psychology, philosophy and artificial intelligence.Their launch was from the mental lexicon, which represents that lexical balance latent in the mind, in which human minds vary, and differ from one stage to another. Building electronic dictionaries, simulating in its work the mental lexicon.